2008
DOI: 10.1111/j.1471-4159.2008.05497.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of bis(monoacylglycero)phosphate and gangliosides in mouse models of neuronal ceroid lipofuscinosis

Abstract: The neuronal ceroid lipofuscinoses comprise a group of inherited severe neurodegenerative lysosomal disorders characterized by lysosomal dysfunction and massive accumulation of fluorescent lipopigments and aggregated proteins. To examine the role of lipids in neurodegenerative processes of these diseases, we analysed phospho‐ and glycolipids in the brains of ctsd−/− and nclf mice, disease models of cathepsin D and CLN6 deficiency, respectively. Both ctsd−/− and nclf mice exhibited increased levels of GM2 and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ). Interestingly, DHA (C22:6, n-3) comprises a signifi cant portion of BMP fatty acids in many cell types in drug-induced phospholipidosis, and also in many LSDs ( 22,(70)(71)(72)(73)(77)(78)(79)(80)(81)(82). We also found that DHA was a major fatty acid species in BMP from the brains of mice, cats, and bears with gangliosidosis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ). Interestingly, DHA (C22:6, n-3) comprises a signifi cant portion of BMP fatty acids in many cell types in drug-induced phospholipidosis, and also in many LSDs ( 22,(70)(71)(72)(73)(77)(78)(79)(80)(81)(82). We also found that DHA was a major fatty acid species in BMP from the brains of mice, cats, and bears with gangliosidosis.…”
Section: Discussionmentioning
confidence: 52%
“…Although BMP comprises a small portion of total phospholipids in normal tissues, BMP levels increase in many LSDs, such as Niemann-Pick, neuronal ceroid lipofuscinoses, mucopolysaccharidosis (MPS I and II), Fabry disease, and Gaucher disease ( 16,17,(19)(20)(21)(22)(23)(24)(25). However, no detailed studies of BMP content and composition have been conducted in the brains of ganglioside storage diseases ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human patients, a slight increase of BMP in brain tissue has been found in some lysosomal diseases such as infantile NCL disease (CLN1), (34, 35), but not in others, including Niemann-Pick disease A in which this lipid is strikingly increased in liver and spleen. The largest increase of BMP in brain tissue reported to date has been in the cathepsin D knockout mouse model of CLN10 disease (23). It should be noted that few mouse models of lysosomal diseases have been investigated with regard to this lipid, and at present, the significance of this finding remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Desalting and separation of total lipids into a neutral and an acidic fraction by reverse-phase chromatography on Bond-elute C18 columns (Varian) and further analytical methods were similar to those used in a previous study (23). For general analysis of the main lipid classes, aliquots corresponding to 2 mg tissue were spotted on high performance thin layer chromatographic (HPTLC) silica gel 60 plates (Merck) developed in chloroform-methanol-water 65:25:4 (v/v/v) and visualized by an anisaldehyde spray.…”
Section: Methodsmentioning
confidence: 99%
“…However, exogenously added BMP can still partly reverse the disease phenotype, [149] and anti-BMP antibodies induce NPC-like state. [153] Although elevations in BMP have been described in some other lysosomal storage disorders, [154] this is by no means a general feature. [155] It seems likely that effective depletion of the anionic lipid BMP by cationic drugs also plays an important role in drug-induced PLD.…”
mentioning
confidence: 98%